Implementation of Combinations for Giving Warm Compress and Breastfeeding to Reduce Post Immunization Pain DPT-HB (DPT COMBO) Independent Midwifery Clinic of Midwife Diana Yulita Aryani at Alian, Kebumen Muhammadiyah Health Science Institute of Gombong - Nur Aini; K Kusumastuti (Prosiding University Research Colloquium, 2019)
Background: During 2016, there were 86% of babies worldwide (116.5 million babies) received 3 doses of diphtheria, tetanus, pertussis (DTP3) vaccine. Pain is one of the side effects of injecting immunization which can cause distress in the baby. Distress behaviour shown by the baby is the way the baby communicates the pain he feels. These events can cause trauma to children, such as anxiety, anger and pain. To overcome this pain can be done by providing warm compresses and breastfeeding. Objective: Finding out the application of a combination warm compress and breastfeeding to reduce pain after DPT-HB immunization (DPT COMBO) In Independent Midwifery Clinic Of Midwife Diana Yulita Aryani. Amd.Keb. Method: The study used a descriptive analytical method with a case study approach. The sample war taken as many as 10 respondents consisting of 5 babies who were not given warm compresses and breastfeeding and 5 babies who were given warm compresses and breastfeeding before DPT-HB immunization, then conducted an assessment of pain response. The instrument uses the FLACC pain scale observation sheet. Data obtained by interviews, observation, and documentation. Result: After applying the combination of giving warm compresses and breastfeeding to reduce pain after DPT-HB immunization (DPT COMBO). All participants who were not given the application of 5 respondents experienced severe pain (100%) while those given the application of 3 respondents (60%) experienced mild pain and 2 respondents (40%) experienced moderate pain.